Cerebrospinal fluid lactate: a differential biomarker for bacterial and viral meningitis in children - Mudasir Nazir; Wasim Ahmad Wani; Muzaffar Ahmad Malik; Mohd Rafiq Mir; Younis Ashraf; Khalid Kawoosa; Syed Wajid Ali (Elsevier, 2018)
Objective: To assess the performance of cerebrospinal fluid (CSF) lactate as a biomarker to differentiate bacterial meningitis from viral meningitis in children, and to define an optimal CSF lactate concentration that can be called significant for the differentiation. Methods: Children with clinical findings compatible with meningitis were studied. CSF lactate and other conventional CSF parameters were recorded. Results: At a cut-off value of 3 mmol/L, CSF lactate had a sensitivity of 0.90, specificity of 1.0, positive predictive value of 1.0, and negative predictive value of 0.963, with an accuracy of 0.972. The positive and negative likelihood ratios were 23.6 and 0.1, respectively. When comparing between bacterial and viral meningitis, the area under the curve for CSF lactate was 0.979. Conclusions: The authors concluded that CSF lactate has high sensitivity and specificity in differentiating bacterial from viral meningitis. While at a cut-off value of 3 mmol/L, CSF lactate has high diagnostic accuracy for bacterial meningitis, mean levels in viral meningitis remain essentially below 2 mmol/L. Resumo: Objetivo: Estudar o desempenho do lactato no líquido cefalorraquidiano como biomarcador para diferenciar a meningite bacteriana da meningite viral em crianças, e definir uma concentração de lactato ótima no líquido cefalorraquidiano que possa ser significativa para a diferenciação. Métodos: Foram estudadas crianças com achados clínicos compatíveis com meningite. O nível de lactato no líquido cefalorraquidiano e outros parâmetros convencionais do líquido cefalorraquidiano foram registrados. Resultados: Em um valor de corte de 3 mmol/L, o lactato no líquido cefalorraquidiano apresentou uma sensibilidade de 0,90, especificidade de 1,0, valor preditivo positivo de 1,0, valor preditivo negativo de 0,963, com uma precisão de 0,972. Os índices de probabilidade positivo e negativo foram 23,6 e 0,1, respectivamente. Para comparação entre a meningite bacteriana e viral, a área abaixo da curva do lactato no líquido cefalorraquidiano foi 0,979. Conclusões: Concluímos que o lactato no líquido cefalorraquidiano possui alta sensibilidade e especificidade na diferenciação da meningite bacteriana da meningite viral. Embora em um valor de corte de 3 mmol/L o lactato no líquido cefalorraquidiano possua alta precisão de diagnóstico da meningite bacteriana, os níveis médios na meningite viral permanecem basicamente abaixo de 2 mmol/L. Keywords: CSF culture, Pneumococcal meningitis, CSF markers, Palavras-chave: Cultura de LCR, Meningite pneumocócica, Marcadores de LCR